Effect of In-Situ Pulse Current on Microstructure and Mechanical Properties of AISI 9310 Gear Steel by Laser Powder Directed Energy Deposition - Cenchao Xie; Fei Yang; Peng He; Wenfa Liu; Qiang Feng; Liucheng Zhou; Ping Liu; Xin Sun (Machines)
AISI 9310 gear steel, renowned for its high hardenability, is widely employed in the manufacturing of aerospace gear components. Laser powder directed energy deposition (LP-DED) takes advantage of a laser heat source to melt metal powder, thus creating a molten pool and facilitating the quick achievement of material deposition and shaping. However, the issue of forming quality has been acting as a significant constraint on the development of LP-DED. To address this concern, the present research endeavors to enhance LP-DED by leveraging the assisted application of in situ pulsed current, with the aim of preparing high-quality deposited specimens. It has been observed that the pulsed current does not trigger any phase transformation within the deposition zone. Instead, the Joule heating effect brought about by the current serves as a catalyst for grain growth. Meanwhile, the electric-plastic effect of the pulsed current results in an elevation of plastic deformation. Moreover, it facilitates the transformation of dislocation defects from simple dislocation lines to intricate dislocation networks, consequently leading to a substantial increase in dislocation density. Furthermore, the contraction force induced by the current exerts a compressive influence on the molten pool, which in turn accelerates the discharge of gas.